Tantangan dan Strategi: Layanan Kesehatan Mental pada Lembaga Pemasyarakatan - Chintia Octenta; Oki Wahju Budijanto Wahju Budijanto; Adi Ashari (Badan Strategi Kebijakan Hukum, 2024)
The 1945 Constitution of the Republic of Indonesia guarantees the right to adequate physical and mental health services for all people without exception, including correctional inmates. However, in reality, to date, several cases of prisoner deaths suspected to be the result of suicide have been recorded in various correctional institutions in Indonesia. Mental health problems have not become a national priority compared to infectious diseases. This study aims to determine and analyze the challenges and policy strategies in providing mental health services for correctional inmates in prisons. The study used a qualitative method with a descriptive approach, which found that the main obstacle was a lack of resources, training and infrastructure. This study highlights the importance of regular training for correctional officers, improved reintegration programs, and regular evaluations to identify best practices and areas for improvement. Overcoming these challenges requires special attention to cross-sector collaboration and policy development, especially to ensure the protection of mental health rights for inmates, as well as facilitating their rehabilitation and reintegration into society, improving risk assessment through training and comprehensive data collection, as well as improving facilities and development. employee professionalism. To overcome this, the author recommends a policy strategy that includes: (1) Short term, namely developing a Grand Design for Mental Health Services, Standard Operating Procedures for emergency conditions, and Integrated Data Collection, (2) Medium term, namely Strengthening Human Resources, Risk Mapping and Standardization of Screening, Improvement of Facilities and 3) Long term, namely creating a reintegration program, conducting regular national evaluations and creating cross-sector collaboration.